Optimization of the PPA Unit in Tegal District Police in Enforcing Law Against Sexual Violence on Children - Vira, Renita (Advances in Police Science Research Journal, 2024)
The background of this research is by the high rate of sexual abuse against children that occurs in the jurisdiction of the Tegal District Police, despite there have been efforts by the Women and Children Protection Unit (PPA Unit) to reduce it. However, the efforts made by PPA Unit have not shown significant results.Therefore, the author conducted research directly in the jurisdiction of the Tegal District Police, with the aim of determining how PPA Unit handles cases of sexual abuse against children and also to identify efforts made to optimize the performance of its members in uncovering cases of sexual abuse against children. The results of the research, which were obtained using the concepts of optimization and Standard Operating Procedures (SOP), show that the efforts made by PPA Unit still need to be maximized. When analyzed using management theory, such as planning, organizing, implementing, and controlling, there are still many areas that do not meet the requirements of the theory. When analyzed using competency theory, there are also deficiencies in the skills possessed by members of PPA Unit due to the large number of members who have not undergone vocational education or development education. Based on the research findings, the author provides problem solving by proposing that PPA Unit members undergo vocational and development education to enhance their ability to prevent sexual abuse against children.